Emerging inorganic solar cell efficiency tables (version 2). (16th April 2021) - Zakutayev, Andriy; Major, Jonathan D; Hao, Xiaojing; Walsh, Aron; Tang, Jiang; Todorov, Teodor K; Wong, Lydia H; Saucedo, Edgardo
Abstract: This paper presents the second version of the efficiency tables of materials considered as emerging inorganic absorbers for photovoltaic solar cell technologies. The materials collected in these tables are selected based on their progress in recent years, and their demonstrated potential as future photovoltaic absorbers. The first part of the paper consists of the guidelines for the inclusion of the different technologies in this paper, the verification means used by the authors, and recommendation for measurement best practices. The second part details the highest world-class certified solar cell efficiencies, and the highest non-certified cases (some independently confirmed). The third part highlights the new entries including the record efficiencies, as well as new materials included in this version of the tables. The final part is dedicated to review a specific aspect of materials research that the authors consider of high relevance for the scientific community. In this version of the efficiency tables, we are including an overview of the latest progress in quasi one-dimensional absorbers, such as antimony chalcogenides, for photovoltaic applications.